MANAGEMENT OF CEREBRAL VENOUS SINUS THROMBOSIS IN PREGNANCY: A CASE REPORT - Gilbert Tangkudung; Ricky Kohar; Corry Mahama; Mieke Kembuan (Jurnal Sinaps, 2019)
We report a case of cerebral venous sinus thrombosis (CVST) in pregnancy. A 26-years-old female with G2P1A0, 30-31 weeks of gestation without regular antenatal care, presented with seizure and unconsciousness, had been admitted to Obstetrics and Gynecology Department. Patient were diagnosed with eclampsia and HELLP syndrome and managed by their protocols. The further management was done an emergency cesarean section. Hemiparesis on the right side was emerged thereafter. The patient then consulted to Neurology Department. The brain non-contrast CT (NCCT) scan was revealed an intracranial hemorrhagic (sICH score=5) and suspected of CVST. The further management was heparinization with strictly controlled of aPTT. The further evaluation of NCCT scan revealed a resolution of intracranial hemorrhagic followed by improvement on neurological deficit and clinical symptoms of HELLP syndrome. Cerebral angiography was revealed a cortical vein thrombosis. Oral anticoagulant was administered, and modified rankin scale (MRS) after being discharged from the hospital was 0. Keywords: management, cerebral venous sinus thrombosis, pregnancy